EFEKTIVITAS EDUKASI VIDEO UNTUK KELENGKAPAN PENJELASAN CARA PENGGUNAAN INHALER OLEH MAHASISWA APOTEKER - Amelia Lorensia; Rifaatul Laila Mahmudah; Ema Arifatul Masruroh; Navaul Setiya Ningrum (jurnal ilmiah manuntung sekolah tinggi ilmu kesehatan samarinda, 2020)
Pharmacists are one of the health workers who play a role in providing information related to explanations of how to use inhaler preparations to asthma patients. This study aims to determine the effectiveness of providing educational videos on how to use several types of inhalers (MDI, MDI with spacers, Diskus®, and Bodyaler® given to pharmacist students. This research is a pre-post design (experimental) study. Sampling was conducted using the method non random sampling using purposive technique, normality test using Shapiro-Wilk and continued.From the results of the data obtained, each assessment verbally (as explained by the subject) and motoric assessment (as demonstrated by the subject) is seen from the pre- and post-intervention Comparing the completeness of explanations both verbally and motorically, showing significant differences compared to before education, with P values ​​for MDI (P (0,000) ≤0.05), MDI with spacers (P (0,000) ≤0.05) Diskus® (P (0,000) ≤0.05), and Turbuhaler® (P (0,000) ,00.05), therefore video education has proven to be effective in increasing student proficiency. self-pharmacist to explain how to use inhalers.